Athletic administration for college, high school, youth and club sport - Gentile, Dina EdD (Jones & Bartlett Learning, 2020)
In order to create, maintain, and sustain athletic programs, sport administrators must be able to analyze problems, develop solutions, craft plans of action, and determine the effectiveness of their decisions. With that in mind, Athletic Administration for College, High School, Youth, and Club Sport explores the skill sets needed to be a successful and effective athletic administrator across diverse sport settings. The content within each chapter speaks to timely issues impacting collegiate sport and student athletes, the changing landscape of high school sport, the challenges of organizing developmental programs in community sport, and the rise in select clubs and leagues in the U.S.